ACL Injuries in the Female Athlete Causes, Impacts, and Conditioning Programs (Springer Berlin Heidelberg, 2018)
This successful book, now in a revised and updated second edition, reviews all aspects of anterior cruciate ligament (ACL) injuries in female athletes, with the focus on complete, noncontact ACL injuries. The opening section discusses anatomy and biomechanics and explains the short- and long-term impacts of complete ACL ruptures, including long-term muscle dysfunction and joint arthritis. Risk factors and possible causes of the higher noncontact ACL injury rates in female athletes compared with male athletes are then discussed in depth. Detailed attention is devoted to neuromuscular training programs and their effectiveness in reducing noncontact ACL injury rates in female athletes, as well as to sports-specific ACL injury prevention and conditioning programs of proven value. Rehabilitation programs after ACL injury and reconstruction that reduce the risk of a future injury are explored, and the concluding section looks at worldwide implementation of neuromuscular ACL injury prevention training and future research directions. The book will be of value to orthopedic surgeons, physical therapists, athletic trainers, sports medicine primary care physicians, and strength and conditioning specialists.